Seed germination strategies: an evolutionary trajectory independent of vegetative functional traits - Hoyle, Gemma L.; Steadman, Kathryn J.; Good, Roger B.; McIntosh, Emma J.; Galea, Lucy M. E.; Nicotra, Adrienne B. (Frontiers in Plant Science, 2015)
1. Seed germination strategies vary dramatically among species but relatively little is known about how germination traits correlate with other elements of plant strategy systems. Understanding drivers of germination strategy is critical to our understanding of the evolutionary biology of plant reproduction. 2. We present a novel assessment of seed germination strategies focussing on Australian alpine species as a case study. We describe the distribution of germination strategies and ask whether these are correlated with, or form an independent axis to, other plant functional traits. Our approach to describing germination strategy mimicked realistic temperatures that seeds experience in situ following dispersal. Strategies were subsequently assigned using an objective clustering approach. We hypothesised that two main strategies would emerge, involving dormant or non-dormant seeds, and that while these strategies would be correlated with seed traits (e.g. mass or endospermy) they would be largely independent of vegetative traits when analysed in a phylogenetically structured manner. 3. Across all species, three germination strategies emerged. The majority of species postponed germination until after a period of cold, winter-like temperatures indicating physiological and/or morphological dormancy mechanisms. Other species exhibited immediate germination at temperatures representative of those at dispersal. Interestingly, seeds of an additional 13 species 'staggered' germination over time. Germination strategies were generally conserved within families. Across a broad range of ecological traits only seed mass and endospermy showed any correlation with germination strategy when phylogenetic relatedness was accounted for; vegetative traits showed no significant correlations with germination strategy. The results indicate that germination traits correlate with other aspects of seed ecology but form an independent axis relative to vegetative traits.